2018
DOI: 10.1111/nyas.13611
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regularities allow saving time for maintenance in working memory

Abstract: Recent evidence suggests that working memory (WM) performance can be enhanced in the presence of an isochronous rhythm during the retention interval because it improves refreshing. Considering the cognitive load (CL) effect as an indicator of refreshing, the present study investigated whether an isochronous rhythm might benefit memory performance under varying cognitive load. For that goal, the presence of a regular rhythm and the cognitive load of the concurrent task (i.e., reading of digits that were either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…We explained earlier that the effectiveness of refreshing depends on temporal factors, but it also could result from developmental differences, as children under 7 years old (e.g., Barrouillet, Gavens, Vergauwe, Gaillard, & Camos, 2009) and healthy older adults seem less able to use this mechanism (Johnson, Mitchell, Raye, & Green, 2004;Fanuel, Plancher, Monsaingeon, Tillmann, & Portrat, 2018a;Plancher, Boyer, Lemaire, & Portrat, 2017). Consistent with the fact that refreshing relies on attention, recent studies have suggested that its efficiency could also be enhanced by providing an isochronous rhythm (known to guide attention over time) during the maintenance interval, something that increases memory performance (Fanuel, Portrat, Tillmann, & Plancher, 2018b;Plancher, Lévêque, Fanuel, Piquandet, & Tillmann, 2018). It could be argued that theories of the existence of attentional refreshing rely mostly on indirect evidence such as the CL effect (see Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012), but Vergauwe and Cowan (2015) provided direct evidence that it consists in reactivating memory traces.…”
Section: Transfer Of Information From Sts To Ltsmentioning
confidence: 99%
“…We explained earlier that the effectiveness of refreshing depends on temporal factors, but it also could result from developmental differences, as children under 7 years old (e.g., Barrouillet, Gavens, Vergauwe, Gaillard, & Camos, 2009) and healthy older adults seem less able to use this mechanism (Johnson, Mitchell, Raye, & Green, 2004;Fanuel, Plancher, Monsaingeon, Tillmann, & Portrat, 2018a;Plancher, Boyer, Lemaire, & Portrat, 2017). Consistent with the fact that refreshing relies on attention, recent studies have suggested that its efficiency could also be enhanced by providing an isochronous rhythm (known to guide attention over time) during the maintenance interval, something that increases memory performance (Fanuel, Portrat, Tillmann, & Plancher, 2018b;Plancher, Lévêque, Fanuel, Piquandet, & Tillmann, 2018). It could be argued that theories of the existence of attentional refreshing rely mostly on indirect evidence such as the CL effect (see Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012), but Vergauwe and Cowan (2015) provided direct evidence that it consists in reactivating memory traces.…”
Section: Transfer Of Information From Sts To Ltsmentioning
confidence: 99%
“…Alternatively, considering the evidence reported in the “Introduction” that regular and irregular timings impact serial order STM tasks, respectively, in a positive and negative direction (e.g., Fanuel et al, 2018; Gorin et al, 2016; Henson et al, 2003; Plancher et al, 2018), one may predict to observe an effect of regularity in this experiment. Consequently, if rhythmic manipulations influence the way serial order is represented in STM tasks, we could expect that, compared with regular sequences, irregular sequences should be recalled less accurately, characterised by an altered pattern of serial order errors, and show a serial position curve reflecting the temporal manipulations implemented in the experiment.…”
Section: Methodsmentioning
confidence: 80%
“…Based on evidences that rhythm can influence performances in STM tasks (positively or negatively, see Fanuel et al, 2018; Gorin et al, 2016; Henson et al, 2003; Plancher et al, 2018; Saito, 1994), it was hypothesised that presenting items with an irregular timing might negatively impact serial recall accuracy and affect error patterns as well. At the same time, if we assume that time plays no role in the representation of serial order as hypothesised in event-based models, one could have made the opposite prediction that timing should not affect serial recall performances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations